A simple technique for mounting crustacean appendages for examination with the scanning electron microscope - Marcos Tavares; Victoria Polit; Christopher C. Tudge (Nauplius)
Abstract A simple, cheap, and yet effective technique to allow easy mounting and imaging of small crustacean (or arthropod) limbs or appendages under the scanning electron microscope using custom-made aluminum mounts, cut from commercial aluminum cans, is explained and illustrated.